2013
DOI: 10.1111/nyas.12160
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol‐based combinatorial strategies for cancer management

Abstract: In recent years, combination chemoprevention is being increasingly appreciated and investigated as a viable and effective strategy for cancer management. A plethora of evidence suggests that a combination of agents may afford synergistic (or additive) advantage for cancer management by multiple means, such as by (1) enhancing the bio-availability of chemopreventive agents, (2) modifying different molecular targets, and (3) lowering the effective dose of agents/drug to be used for cancer management. Resveratrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 48 publications
1
83
0
Order By: Relevance
“…Res is a natural polyphenol and has been demonstrated to act as a promising antitumor agent (6). Although Res has been shown to have suppressive effects on several types of human malignancies in vitro and in vivo, its chemotoxic effect on chondrosarcoma cells as well as the molecular mechanism remains largely unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Res is a natural polyphenol and has been demonstrated to act as a promising antitumor agent (6). Although Res has been shown to have suppressive effects on several types of human malignancies in vitro and in vivo, its chemotoxic effect on chondrosarcoma cells as well as the molecular mechanism remains largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence regarding its activity reveals that Res has an effect on cell proliferation, differentiation, apoptosis and autophagy (4,5). Furthermore, it has been demonstrated that Res has a suppressive effect on various types of human malignancy (6). For instance, Yang et al (7) reported that Res inhibited the growth of gastric cancer by inducing G1 phase arrest and senescence.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Res plays an antagonistic role in numerous tumors, including gastrointestinal cancer (14,15). Recently, Yang et al (16) showed that Res inhibits the growth of gastric cancer cells by inducing G1 phase arrest and senescence in a Sirt1-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of resveratrol include anti-oxidant and anti-aging properties, improvement of insulin sensitivity and reduction of cardiovascular disease risk (9-11). Previous studies have also indicated that resveratrol is able to function as a chemo preventive and chemotherapeutic agent in certain types of human carcinomas, including those of the colorectum, skin, liver, lung, pancreas, breast and prostate (8,(12)(13)(14). Previous studies suggesting that a dietary pattern rich in resveratrol may reduce the risk of ESCC (15).…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanisms underlying resveratrol-induced antitumor effects have yet to be elucidated. A number of potential mechanisms have been suggested to be involved in resveratrol-induced cancer preventative effects, including the inhibition of tumorigenesis-associated transcription factor activation, the suppression of various protein kinases and the regulation of the expression of specific genes involved in cell cycle progression, apoptosis, angiogenesis and metastasis (8,12,(16)(17)(18).The epidermal growth factor receptor (EGFR) is a receptor tyrosine kinase that mediates intracellular signaling in response to various extracellular stimuli (19 …”
mentioning
confidence: 99%